Implementasi Business Intelligence System pada Restock Gudang Farmasi PT. Pentavalent Menggunakan Algoritma NaÃ¯ve Bayes - Nurjoko, Nurjoko; Negara, Fuzy Komala Sari (Politeknik Negeri Sriwijaya, 2021)
Abstract The work in handling drug requests is carried out routinely and repeatedly. Business Intelligence (BI) is able to help the healthcare industry improve service quality, reduce costs, and manage risk. To maximize performance and effectiveness in the medical and health fields, one of them is that the data must be managed properly into information. The medical process which is a health service practice, although this is not the only activity in the pharmacy warehouse, but in the end this activity is more likely to have an indirect impact on medical and business activities. Business Intelligence (BI) will be used for processing, analyzing and distributing data at PT Pentavalent's pharmaceutical warehouse activities, especially the drug request process. In this study, we will try to analyze drug demand transaction data at PT Pentavalent using the Naive Bayes Algorithm and RapidMiner tools which later the results of the data analysis will be used as a decision supporter for PT Pentavalent in providing medicines according to the pharmacy's request. The Naive Bayes Algorithm method is able to provide good results and can be used for data processing grouping and prediction of the need for more precise and accurate amounts and types of drugs, as a reference for decision support in providing and distributing medicines according to pharmacy requests. The accuracy value is based on the level of closeness between the predicted value and the actual value of 15.62%. Keywordsâ€” PT Pentavalent, Business Intelegent, OLAP, Â Algoritma NaiveBayes